Epistemology of Mantuq and Mafhum for Critical Thinking in Islamic Education - Nofrizal Nofrizal; Syahruddin Syahruddin; Yanfaunnas Yanfaunnas; Mahyudin Ritonga; Rusydi AM (International Journal of Multidisciplinary Research of Higher Education, 2026)
The cultivation of critical thinking skills is a central demand of 21st-century education. Within Islamic education, this development must be anchored in the epistemological tradition of usul al-fiqh, particularly through the reasoning instruments of mantuq and mafhum. This study reconstructs these concepts as an epistemological foundation for critical thinking by proposing the Critical Islamic Reasoning Framework . Employing a qualitative library-based research design, the study applies content analysis to classical usul al-fiqh texts and contemporary scholarship on critical thinking and Islamic education. The analytical process involved concept identification, categorization, synthesis, and interpretation to reveal the relationship between mantuq, mafhum, and critical thinking indicators. Findings demonstrate that mantuq operates as a tool for textual recognition of explicit meaning, while mafhum functions as a mechanism for contextual interpretation of implicit meaning. Both are reinforced by logical verification, ethical reflection, and contextual application. The synthesis produces the CIRF model, integrating revelation, reason, and reality as the epistemological basis for critical thinking. This study expands the role of mantuq and mafhum beyond legal deduction, positioning them as a conceptual framework for critical thinking education relevant to contemporary Islamic educational development.